A remark on polynomial norms and their coefficients. Issue 1 (2000) - Kim, Sung Guen
Abstract : This paper presents new lower bounds for the norms of 2-homogeneous real-valued polynomials onl p spaces for0 < p ≤ ∞ which are sharper than those recently given by the author.